2005
DOI: 10.1007/s10608-005-3888-0
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Coping with Dysphoric Mood: Contrasts with Rumination and Distraction

Abstract: Past research has shown that rumination exacerbates dysphoric mood whereas distraction attenuates it. This research examined whether the practice of mindfulness meditation could reduce dysphoric mood even more effectively than distraction. A dysphoric mood was induced in 139 female and 38 male participants who were then randomly assigned to a rumination, distraction, or meditation condition. As predicted, participants instructed to meditate reported significantly lower levels of negative mood than those in eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
199
2
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(224 citation statements)
references
References 30 publications
(20 reference statements)
17
199
2
6
Order By: Relevance
“…The attenuating effects of mindfulness on subjective emotional intensity observed in the present study are consistent with the view that mindfulness-based strategies promote emotional stability and constitute an efficient means of emotional self-regulation (Arch and Craske, 2006;Broderick, 2005). Indeed, the present findings suggest that mindful awareness fosters a more adaptive, relaxed, and objective manner of responding to emotional situations as opposed to habitual, automatic, and conditioned reaction patterns.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The attenuating effects of mindfulness on subjective emotional intensity observed in the present study are consistent with the view that mindfulness-based strategies promote emotional stability and constitute an efficient means of emotional self-regulation (Arch and Craske, 2006;Broderick, 2005). Indeed, the present findings suggest that mindful awareness fosters a more adaptive, relaxed, and objective manner of responding to emotional situations as opposed to habitual, automatic, and conditioned reaction patterns.…”
Section: Discussionsupporting
confidence: 91%
“…Focused-breathing typically practiced during mindfulness has been shown to promote emotional self-regulation by reducing reactivity to emotionally laden pictures (positive and negative) (Arch and Craske, 2006). Mindfulness meditation practiced following a sad mood induction was also shown to decrease dysphoric mood states (Broderick, 2005). Additionally, Brefczynski-Lewis et al (2007) found a negative correlation between the number of hours of meditation training and NeuroImage 57 (2011NeuroImage 57 ( ) 1524NeuroImage 57 ( -1533 right amygdala activation during concentration meditation in a group of experienced meditators while processing negative emotional sounds.…”
Section: Introductionmentioning
confidence: 96%
“…These findings further bolster the idea that impermanence focus plays a causal role in decreasing stress reactivity. They are also broadly consistent with research demonstrating that mindfulness training-a component of which involves learning to perceive thoughts and feelings as transitory events in the mindreduces emotional reactivity to negative events (e.g., Britton, Shahar, Szepsenwol, & Jacobs, 2012;Broderick, 2005). However, the present research is the first to suggest that placing negative events into a more distant time perspective may heighten awareness of their impermanence in a manner similar to adopting a mindful, present-oriented focus.…”
Section: Discussionsupporting
confidence: 89%
“…However, the causal direction of this relation is uncertain in these studies. While a broad-based disposition (mindfulness) is more likely to influence a specific behavioral tendency (gambling) than the converse, experimental research is warranted, possibly using mindfulness induction (e.g., Broderick, 2005). Finally, the risk-taking tasks we employed did not offer wagers for real money, and differed from real gambling in other ways.…”
Section: Discussionmentioning
confidence: 99%